Penerapan Metode Kendali Aliran Sebagai Upaya Pelestarian Sumber Daya Air Di Pondok Pesantren Nurul Haramain - Ibnu Hajar; I Made Indradjaja Marcus Brunner; Dhami Johar Damiri; Martin Choirul Fatah; Yuliansyah Yuliansyah; Jumiati Jumiati (Sekolah Tinggi Teknik - PLN, 2023)
Environmental damage can be caused by an imbalance of the earth’ constituent elements, which one of the elements is scarcity of clean water in the earth. Dearth of clean water is predicted that will be experienced more than a half of word population of nine million of human being in 2050. The phenomenon of the scarcity of the clean water has been occurred especially in Indonesia that it is a country which has six percent of the potential of the clean water, but in fact it shows the need of the clean water of Indonesia population are still not enough. The dearth of the clean water needs to get serious attention from all stake holder, included people in the boarding school. An effort to decrease the scarcity of the clean water rate is by behaving frugally in using the clean water. To do that need to do socialization massively to the people and it require a long time. Therefore, beside the socialization massively, engineering to decrease the flow rate in using the clean water through the valves that is by applicating flow control method. This simple technology of flow control application, the community service team and Nurul Haramain boarding school located in Kampung Saitem, Ciburayut, Cigombong, Bogor, West Java are collaborated. A measurement result of flow rate before the flow restrictor is applicated in the valve is 7.76 liter/minute and after applicated decrease to 1.13 litter/minute. Percentage of decreasing is to reach 83 percent.